COMPARATIVE EVALUATION OF THE ACADEMIC PERFORMANCE OF SINGLE SEX AND CO-EDUCATIONAL SECONDARY SCHOOL STUDENTS IN IBADAN, SOUTH WEST NIGERIA (2016)
This study compared the performance levels of students of single-sex schools against coeducational schools at the end of the third year of senior secondary education in Ibadan, South West Nigeria. Three hypotheses were tested using primary data gathered from Multilevel analysis which was carried out on a sample of approximately 300 secondary school students